Plan exportador de cacao procedente de Coper, Boyacá - Reyes Nieto, Danna Katherine (Universidad Antonio Nariño, 2021)
Colombia has climatic and land conditions, ideal fields for the production of fine-grain, soft cocoa and an excellent aroma. Therefore, in the world and within international trade; This product, especially Colombian, is recognized for being of high quality, as is Colombian Coffee, except that cocoa has not had great support from the government; encouraging production and processing. According to Procolombia, fine and aromatic cocoa is a category that groups only 5% of the world-wide commercialized bean (International Cocoa Organization, ICCO). And in the case of Colombia, this bean is select and exclusively for the production of fine chocolates due to its acidity and balance.